Study on the Applicability of an Improved Pile-Beam-Arch Method of Metro Station Construction in the Upper-Soft and Lower-Hard Stratum - Xinping Guo; Annan Jiang; Shanyong Wang (Advances in Civil Engineering)
The main challenge for metro station construction is to ensure the construction schedule while minimizing the impact on the surrounding environment. Based on the characteristics of the upper-soft and lower-hard stratum in the Dalian city of China, a special structure with six pilot tunnels and three spans of the pile-beam-arch (PBA) method is proposed and applied to the construction of the Labor Park metro station. In this study, laboratory experiments, numerical simulation analysis, and field monitoring data are used to investigate the applicability of six pilot tunnels and three spans of the PBA method in the process of construction. In the process of numerical simulation, the ground surface settlement, arch vertical displacement, the horizontal displacement of rock mass on both sides of the station, and vertical stress of support structure are analyzed. The numerical simulation results are found to be in good agreement with field measurement. Furthermore, the results indicate that, in the construction of six pilot tunnels and three spans of the PBA method, pilot tunnel construction and arch construction have a great influence on the surface settlement. The part of the initial vertical support of the pilot tunnels is removed, which caused the change of the position of maximum vertical stress and the redistribution of vertical stress. Because of reinforcement by side piles on both sides of the station, the horizontal displacement of the rock mass was reduced by 44.76% compared with that without reinforcement. The six pilot tunnels and three spans of the PBA method can effectively control the surface settlement, arch vertical displacement, and horizontal displacement of the rock mass.